Perencanaan dan Perancangan Perpustakaan Milenial di Kota Denpasar - I Putu Yogi Wiliawan Wiliawan; I Wayan Parwata; Ni Wayan Nurwarsih (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2022)
In Indonesia, the literacy level of the people is quite low. This is because people, especially millennials, are still reluctant to visit the library, because they are considered rigid, formal and monotonous. In addition, the many locations of libraries that are less strategic make the building less accessible to the public. With this issue, it is hoped that there will be a library facility in Denpasar City with an atmosphere that gives an image like young people, which is comfortable, flexible but still attracts attention. With several supporting facilities to attract public interest, especially millennials, to visit to read, express creativity, or as a medium of entertainment.